Emotional Intelligence and Clinical Performance in Psychiatric Nursing Students - Ycaza, Sherwin (MALATA SAINS INDONESIA, 2024)
Emotional Intelligence (EI) has gained considerable attention in nursing due to its positive effects on nurses' well-being and its beneficial impact on patients and families. Emotional intelligence involves understanding and managing one's own emotions and the emotions of others, which is crucial for nurses who build relationships with patients, families, and healthcare team members. Despite the recognised importance of emotional intelligence, non-academic factors like emotional intelligence are rarely considered in nursing program admissions, with GPA being the primary indicator of academic performance. Given the limited studies on emotional intelligence and academic performance in the Philippines, this study aimed to determine the relationship between nursing students' emotional intelligence and their psychiatric nursing clinical practice performance. This study employed a descriptive correlational design and included a substantial sample of 173 fourth-year nursing students who completed their psychiatric nursing clinical practice and were enrolled in the academic year 2017. Total population sampling was utilised, ensuring a comprehensive representation of the student population. The Pearson product-moment correlation coefficient (Pearson-r) was used to determine the correlation between emotional intelligence and clinical performance. The results, based on these methods, indicated that all respondents had moderate to high levels of emotional intelligence. Nearly half of the respondents achieved a satisfactory grade, with the majority having average to satisfactory performance. Female respondents had slightly higher grades than male respondents, and there was a significant difference in performance based on the respondents' school but not their age. Importantly, there was no significant correlation between emotional intelligence and clinical performance in psychiatric nursing, a finding that was consistent with the literature. This insight is valuable for educators and curriculum developers, as it underscores the need to consider a broader range of factors beyond academic performance in nursing education. It also highlights the importance of providing support and resources to enhance students' emotional intelligence skills. Further research is recommended to explore the role of emotional intelligence in nursing education and consider additional factors that may influence academic and clinical performance.